Two new species of the genus Sinopodisma Chang, 1940 (Orthoptra, Acridoidea, Catantopidae, Podisminae) from Taiwan, China - Ye, Bao-Hua; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2017)
Two new species of the genus Sinopodisma Chang, 1940 from Taiwan, China are described in this paper. The new species Sinopodisma orchofemura sp. nov. is similar to Sinopodisma kodamae (Shiraki, 1910), but differs from latter in antennae length of joint 2.9 times width in the middle part, hind femur yellow, length of interspace of mesosternum larger than narrowest, tegmina almost reaching the hind margin of second abdominal tergum. The Sinopodisma hsinchuensis sp. nov. is similar to Sinopodisma orchofemura sp. nov., but differs from latter by vertical diameter of eyes 1.7 times horizontal diameter and 1.8 times subocular furrow; tegmina extending over the hind margin of first abdominal tergite slightly; the length of interspace of mesosternum equal to narrowest and subgenital plate longer than ovipositor valves ventral view. Type specimens are deposited in the National Museum of Natural Science, Taichung, Taiwan, China and the Institute of Entomology, Taiwan University, Taibei, Taiwan, China respectively.